Improving the sensitivity of in vitro skin penetration experiments - Kasting, G B; Filloon, T G; Francis, W R; Meredith, M P (Pharmaceutical research, 1994)
The institution of a readily-implemented sample screening and data handling procedure for in vitro skin penetration studies yields substantial improvements in sensitivity for distinguishing between formulations, treatments, penetrants, etc. The procedure involves four steps: 1) prescreen the tissue samples to determine their intrinsic permeability; 2) apply treatments using a randomized complete block (RCB) design, with blocking by tissue permeability; 3) apply a variance-stabilizing transformation to the penetration data, followed by outlier testing; and 4) analyze the transformed data according to an RCB analysis of variance, using tissue permeability as the blocking variable. For penetration studies in which high sample variability is a concern, the above procedure commonly yields a sensitivity advantage of several-fold versus alternative methods of comparison.